Within the Enemy’s Camp: contribution of the granuloma to the dissemination, persistence and transmission of Mycobacterium tuberculosis - Shaler, Christopher R.; Horvath, Carly; Jeyanathan, Mangalakumari; Xing, Zhou (Frontiers in Immunology, 2013)
Pulmonary tuberculosis, caused by Mycobacterium tuberculosis (M.tb) represents a leading global health concern, with 8.7 million newly emerging cases, and 1.4 million reported deaths annually. Despite an estimated one third of the world’s population being infected, relatively few infected individuals ever develop active clinical disease. The ability of the host to remain latently infected while preventing disease is thought to be due to the generation of a robust type 1 immune response in the lung, capable of controlling, but not clearing, M.tb. A key feature of the type 1 immune response to M.tb is the formation of immune cellular aggregates termed granuloma. The granuloma structure has long been considered a hallmark of host’s protective response toward M.tb. Historically, a correlative relationship between granuloma formation/maintenance and bacterial control has been seen in models where disrupted granuloma formation or structure was found to be fatal. Despite this established relationship much about the granuloma’s role in M.tb immunity remains unknown. Recent publications suggest that the granuloma actually aids the persistence of M.tb and that the development of a necrotic granuloma is essential to person-to-person transmission. Our group and others have recently demonstrated that enclosed within the granuloma is a population of immunologically altered antigen-presenting cells and T lymphocyte populations. Of note, the ability of these populations to produce type 1 cytokines such as interferon-gamma, and bactericidal products including nitric oxide, are significantly reduced, while remaining competent to produce high levels immunosuppressive interleukin-10. These observations indicate that although the chronic granuloma represents a highly unique environment, it is more similar to that of a tumor than an active site of bacterial control. In this review we will explore what is known about this unique environment and its contribution to the persistence of M.tb.